First Language Development on Children: The Literature Review Analysis - Korompot, Siti Astini (English Education Department, 2023)
This article aims to observe about how children was acquiring and developing their first language. Most of the theorist agreed that mostly children acquire their language through several steps. They are Prelinguistic stage, babbling stage, one-word stage, two-word stage, telegraphic stage and multi-word stage. This research used literature review analysis to explore the detail explanation about first language development on children. It based on the theory of behaviorist, nativist, and interactionist. Behaviorist explained that language is learned through environmental conditioning and imitation of adult’s model. Nativist said that language is native, natural, and innate to human beings. Every child is born with a ‘built in’ device for acquiring language. In other explanation, iinteractionist said that language is a product of both genetic and environmental factors. This research contributed to the understanding of first language development and implicated to the understanding of second language development for children. It can be used to overviewed the second language learning.